Proceedings of the 2019 on Designing Interactive Systems Conference 2019
DOI: 10.1145/3322276.3322281
|View full text |Cite
|
Sign up to set email alerts
|

Designing Interactive Manual Wheelchair Skills Training for Children

Abstract: Access to wheelchair skills training is important for the mobility and independence of wheelchair users, but training rates are low-particularly among young people. In this paper, we present Geometry Wheels, a movement-based experience prototype to explore the potential of interactive technology to support basic wheelchair skills training for manual wheelchair users, designed with the support of occupational therapists. Results of an evaluation with 15 participants (10 young wheelchair users and 5 parents) sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Parents of young children often feel uncertainty and require resources to support their children's changing needs [32]. Despite the emphasis in research on family centeredness in services for children [33,34], studies have found a lack of reasoned consideration given to supports that meet different family needs [32,35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents of young children often feel uncertainty and require resources to support their children's changing needs [32]. Despite the emphasis in research on family centeredness in services for children [33,34], studies have found a lack of reasoned consideration given to supports that meet different family needs [32,35].…”
Section: Introductionmentioning
confidence: 99%
“…Parents of young children often feel uncertainty and require resources to support their children's changing needs [32]. Despite the emphasis in research on family centeredness in services for children [33,34], studies have found a lack of reasoned consideration given to supports that meet different family needs [32,35]. Currently, limited research exists that investigates the effectiveness of, and best practice in developing, manual wheelchair skills training and education for children, with no current standardized protocol [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%